Peran Pendidikan Islam dalam Pelaksanaan Otonomi Pendidikan di Indonesia - Firman Mansir (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
This article describes the role of Islamic education in the implementation of educational autonomy that occurs in Indonesia, both in Islamic educational institutions and in general education institutions. The results of the study indicate that Islamic education plays a major role in the implementation of educational autonomy. This is because Islamic education is a separate part that is able to implement its curriculum in Islamic educational institutions. This research is a literature study so that the data analyzed are sourced from various literature references by using literature analysis in revealing the data. Thus, the implementation of educational autonomy in various Indonesian educational institutions goes well together in accordance with the educational and learning objectives to be achieved. In the context of Islamic education itself, the entire PAI curriculum is able to synergies with other subjects implemented in schools and madrasa.